Body Mass Index can be a Good Predictor of Bone Mineral Density in Postmenopausal Women in India - Biplob Chowdhury; Brajanath Kundu (Intelektual Pustaka Media Utama, 2014)
Risk factors for the prediction of osteoporosis are an important and cost effective method since osteoporosis is a silent disease. The purpose of the study was to evaluate the associations between weight, body mass index (BMI), the Osteoporosis Self-Assessment Tool (OST), and bone mineral density (BMD) in postmenopausal women in India. In this cross sectional study, 90 postmenopausal women aged 45–85 years who had given consent participated and the study was conducted between April, 2012 and May, 2013. BMD was measured by ultrasound bone densitometry at calcaneal site. Linear regression multivariate models were used to examine the associations with weight, BMI, OST, and BMD. Body weight, BMI, and OST had almost similar overall performance in their ability to classify women with BMD T-score ≤−2.5. Regression results showed that the linear combination of three independent variables BMI, OST and body weight. BMI predicted 65.7% of the variance in BMD, R2 = .657, R2 adjusted = .609, (F=21.295, p<.000). The strongest predictor of low BMD was BMI. BMI showed significant association with BMD with a correlation of .846. Low weight and BMI predict osteoporosis and are associated with increased risks in postmenopausal women. The negative impact of low body weight on bone health should be more widely recognized.